ANALYSIS OF CONTENT IN PEDAGOGICAL WORK - Henryk, NOGA (Trends in education, 2014)
The need for diagnosis in pedagogy and psycho pedagogy has been highlighted by many authors so far. Diagnosis is the basis of all kinds of actions: preventive, corrective, and compensatory or aid. One of very effective but underestimated research methods is content analysis. It has been known and used for several decades in literary studies, press studies, sociology and political science. The method, hardly ever used in pedagogy, could bring excellent research results as teachers and educationalists often have the possibility to use a variety of texts which can become a source of knowledge supporting the whole educational process and clarifying its different mechanisms.
Keywords: psycho pedagogic diagnosis; research; content analysis.